PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN USAHA MIKRO KECIL MENENGAH PADA USAHA LAUNDRY DUA SAUDARA DI KAMPUNG GARDU KELURAHAN BUARAN KECAMATAN SERPONG - Syamsul Mu Arif; Lindawati Lindawati; Wulandari Cahyani Putri (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
The aim of Community Service Activities is not only to implement one of the Tri Darmas of Higher Education but more than that, namely to be able to make a real contribution, especially to the community within Pamulang University. As the growth rate of MSMEs increases, MSME players around Pamulang University are increasingly aware of the importance of preparing simple financial reports. This simple financial report is considered financial information in maintaining transparency at each level of the business process so that it complies with appropriate standards and MSME players know the size of the profits from the business they are running. For MSME players, making simple financial reports is considered a complicated matter. Apart from that, the knowledge of MSME actors is also very limited, the lack of understanding of accounting knowledge, the lack of technological knowledge, the lack of funds and equipment at their disposal make it difficult for the Two Brothers Laundry MSME actors to prepare adequate financial information. Therefore, this PKM activity for Pamulang University lecturers was carried out to provide training for the Two Brothers Laundry MSMEs in Kp. Buaran Serpong sub-district substation. This financial report preparation training is designed to develop human resources through the preparation stage, implementation stage and evaluation stage and later MSME players will utilize an accounting system that can be used continuously as long as the business runs. The results of this PKM activity can be published in the PKM journal with ISSN.